Catalogue of electron precipitation events as observed in the long-duration cosmic ray balloon experiment. (November 2016) - Makhmutov, V.S.; Bazilevskaya, G.A.; Stozhkov, Yu.I.; Svirzhevskaya, A.K.; Svirzhevsky, N.S.
Abstract: Since the International Geophysical Year (1957), the Lebedev Physical Institute performs the regular measurements of charged particle fluxes in the Earth's atmosphere (from the ground level up to 30–35 km) at several latitudes. The unique experimental data base obtained during 58 years of cosmic rays observations in the atmosphere allows to investigate temporal, spatial and energetic characteristics of galactic and solar cosmic rays as well as the role of charged particles in the atmospheric processes. Analysis of this data base also revealed a special class of numerous events caused by energetic electron precipitation recorded in the atmosphere at polar latitudes. In this paper we present Catalogue of electron precipitation events observed in the polar atmosphere during 1961–2014 and briefly outline the previous results of this data set analysis. Highlights: Regular measurements of cosmic rays in the Earth's atmosphere (0–35 km) since 1957. A special class of events caused by energetic electron precipitation at polar latitudes is defined. More than 550 events of precipitating electron events are recorded during 58 years of observations. Characteristics of precipitating electron spectra are determined. We present the Catalogue of electron precipitation events observed during 1961–2014.